Differential antibody isotype expression to the major Paracoccidioides brasiliensis antigen in juvenile and adult form paracoccidioidomycosis - Baida, H.; Biselli, P. J. C.; Juvenale, M.; Del Negro, G. M. B.; Mendes-Giannini, Maria José Soares [UNESP]; Duarte, A. J. S.; Benard, G. (Elsevier B.V., 1999)
We investigated the relationship between antibody response to the major Paracoccidioides brasiliensis antigen, a 43-kDa glycoprotein, and the two paracoccidioidomycosis (PCM) clinical presentations, the juvenile and the adult forms. Total immunoglobulin G (IgG), IgG isotypes, and IgA anti-gp43 antibodies were determined by enzyme-linked immunosorbent assay in patients' sera. Juvenile PCM patients had higher (P =.003) IgG anti-gp43 levels than adult form patients. IgG1 subclass levels, however, were comparable between the two clinical forms. Patients with the juvenile form had higher (P <.001) IgG4, but lower(P =.03) IgG2 levels than patients with the adult form. The IgG4 isotype, regulated by interleukin 4, was found in all juvenile form patients but in only 12% of the adult form patients. In contrast, high levels of the IgG2 isotype, regulated by interferon-gamma, were found in 41% of the adult PCM patients, mainly those with a more benign disease, but in only 12% of the juvenile patients. IgG3 was either absent or detected at low levels. These results demonstrate, for the first time, specific IgG4 antibodies in the humoral immune response of patients with an endemic deep mycosis and suggest that the switch to the IgG subclasses in PCM is regulated by the patients' T-helper subset (Th-l or Th-2) dominant cytokine profile. A possible role for IgG4 in the immunopathogenesis of the juvenile, more severe form of the disease is discussed. Finally, IgA was found mainly in adult form patients, probably as a result of the chronic mucosal antigenic stimulation characteristic of this form. (C) Elsevier, Paris.
Keywords: paracoccidioidomycosis; immunoglobulin isotypes; Paracoccidioides; serology; IgA